Expanding the frontiers of visual analytics and visualization - Earnshaw, Rae; Kasik, David; Vince, John; Wong, Pak Chung; Dill, John (Springer London, 2012)
The data deluge problem is increasing. Every day the results of scientific experiments, monitoring instruments, medical analysis, and social networks add petabytes to the world's information. Many future experiments will generate data that will be substantially more than has been collected throughout history. How can we effectively translate this into meaningful information, particularly if there is a time critical element to the data? Although Moore's law results in an ever-decreasing cost of processing, storage, and transmission - so that the data can be stored and transmitted - it does not necessarily follow that the data can be processed effectively. Visual analytics seeks to facilitate analytical reasoning supported by interactive visual interfaces in order to integrate the human into the analysis process. Expanding the Frontiers of Visual Analytics and Visualization contains international contributions by leading researchers from within the field. Dedicated to the memory of Jim Thomas, the book begins with the dynamics of evolving a vision based on some of the principles that Jim and colleagues established and in which Jim's leadership was evident. This is followed by chapters in the areas of visual analytics, visualization, interaction, modelling, architecture, and virtual reality, before concluding with the key area of technology transfer to industry. Visual analytics and visualization bring together the areas of computer science, information visualization, cognitive and perceptual sciences, interactive design, graphic design, and social sciences.